Influence of surface and subsurface Co–Ir alloy on the electronic properties of graphene. (15th October 2021) - Wang, Kangli; Vincent, Thomas; Bouhiron, Jean Baptiste; Pons, Stephane; Roditchev, Dimitri; Simon, Sabina; Fonin, Mikhail; Paulus, Beate; Dedkov, Yuriy; Vlaic, Sergio; Voloshina, Elena
Abstract: Using density functional theory (DFT) calculations and angle-resolved photoemission spectroscopy (ARPES) the structural and electronic properties of graphene on the surface and subsurface Co–Ir alloy are investigated upon the intercalation of Co in graphene/Ir(111). It is found computationally that the interaction strength between graphene and substrate is strongly affected by the composition and nature of an alloy, implying the large difference in the electronic structure of monolayer graphene on Co x Ir1− x /Ir(111) and Ir/Co x Ir1− x /Ir(111). Our theoretical results are supported by ARPES data, which demonstrate the disappearance of the Dirac cone when graphene lies on Co and its restoration upon the formation of the subsurface Co–Ir alloy. Graphical abstract: Image 1 Highlights: The composition and position of CoIr alloy affects the graphene layer morphology. The presence of Co at the interface tends to destroy the Dirac cone. The Dirac cone is preserved if subsurface Co–Ir alloy is formed.